Clinical Management of Hypodontia of Two Mandibular Incisors - Sergio Paduano; Lorenza Barbara; Domenico Aiello; Marianna Pellegrino; Felice Festa (Hindawi Limited, 2021)
This article presents the clinical management of a patient with bilateral congenitally missing mandibular incisors. This condition is relatively rare and always needs a careful diagnosis and treatment planning. The chosen treatment strategy for this patient included space closure by protraction of the mandibular posterior teeth and canine substitution of missing incisors. Furthermore, the problems arising from this treatment plan, such as premolar-protected occlusion and tooth size discrepancy, are discussed. From the case presented in this study, we can conclude that space closure may be considered an efficient treatment approach for achieving satisfactory functional and aesthetic results.